Melodic and textual resource materials in A. T. Olaolude’s Mayokun (2020)
This paper examines the compositional resource materials of Yoruba native airs (YNAs) composed by Rev. A. T. Ola Olude in his Yoruba hymn book Mayokun. Several Yoruba native air composers have contributed greatly to the development of the YNAs in Christian liturgy, which was as a result of the need for hymns that best represent the Yoruba identity since there was a clash between the speech tone of the Yoruba texts and the European hymn melodies of the translated European hymns. This paper established four compositional resource materials used in Mayokun the Yoruba hymn book. Rev. Ola Olude adapted Yoruba folktales and ceremonial melodies to which he added newly composed text in idiomatic Yoruba language reflecting Christian doctrine. In addition, he adapted and made parody of Yoruba drum language in form of speech surrogacy. He also composed melodies in Yoruba idioms to the first verse of translated European hymns and in addition, he composed entirely original hymns in both text and tune